The Influence of Digital Literacy and Adaptive Leadership Style on Human Resource Performance Through Technology Readiness as for Outsourching Employees of ULP Cibadak West Java - Eka Rahma Daniati; Elfitra Desi; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of Digital Literacy and Adaptive Leadership Style on Human Resource Performance through Technology Readiness among outsourced employees at ULP Cibadak, West Java. A total of 166 employees were selected using purposive sampling. The analysis was conducted using Partial Least Square (PLS) to test validity, reliability, and both direct and indirect effects between variables. The results indicate that Digital Literacy has a positive and significant effect on both Technology Readiness and Human Resource Performance, while Adaptive Leadership Style significantly affects Technology Readiness but not directly Human Resource Performance. Technology Readiness was found to mediate the relationship between Digital Literacy and Adaptive Leadership Style with Human Resource Performance. These findings highlight the importance of enhancing digital literacy and adaptive leadership to support technology readiness and improve HR performance in outsourcing environments.